VENTRICULAR ARRHYTHMIA (VARD) OR VENTRICULAR TACHYARRHYTHMIA (VTA) - Raxmonov Mexroj; Osmanov Tamal; Aliyev Alisher; Aminov Azimjon (Journal of Science in Medicine and Life, 2024)
The general name of heart rhythm disorders, in which the source of ectopic activity or re-entrant circle is located under its bundle, i.e. in its branches, Purkinje network or ventricular myocardium. During the ECG, ventricular extrasystole is recorded in the form of single impulses in about 5% of healthy young people, and during daily ECG monitoring - in 50% of subjects, which is the norm. With age, ventricular extrasystole is often detected